Prime riflessioni sul pensiero di Paolo Grossi in tema di costituzionalismo - Cucullo, Alessia (Studi Politici, 2023)
This article is aimed to provide some considerations on the theme of constitutionalism in Paolo Grossi’s thought. After proposing a brief recap concerning modern and pos-modern, focus will be directed on the research of the carnality of law, going beyond the concept of the individual as a human model. The idea of law, as a dogma, is abandoned in order to take in it as an instrument aimed to bringing order in society. This idea in Italy is realized by the 1948 Constitution, which is presented to the citizen – as Paolo Grossi pointed out – as a legal breviary, a breviary of life. The Constitution is an authentically democratic instrument that incorporates those values, those principles that surely find consensus among all people. The Constitution represents, therefore, an instrument that makes those principles so impenetrable that it provides an instrument of control, able to limit legislative power where it conflicts with the fundamental rights.